Stakeholders in the local service centre: who should be involved in the planning process? Insights from Poland, Czech Republic and Denmark - Damurski Łukasz; Pluta Jacek; Maier Karel; Andersen Hans Thor (Bulletin of Geography. Socio-Economic Series, 2019)
Local service centres play a vital role in shaping the quality of life in urban neighbourhoods. They offer access to essential everyday services (shops, education, healthcare, personal services) and to public spaces. If they are properly planned and managed, they can bring particular added values to a local community, such as social integration and territorial identification. The history of urban planning has produced several patterns of local service centres (ancient agora, mediaeval market square, neighbourhood unit, modern agora) but today a question arises: how can a local service centre be successfully planned and organised in post-modern political practice? How can its potential be realised and the ever-changing needs, expectations and preferences of local communities be met? Who should be involved in those processes? To answer those questions in this paper we refer to citizen participation and public communication concepts, where selecting the appropriate stakeholders emerges as a necessary starting point for effective urban governance. We present the results of in-depth interviews with local actors (local authorities, municipality officials, town planners, non-governmental organisations, local leaders) in Poland (Wrocław, Siechnice, Ostrów Wielkopolski, Warszawa and Zabierzów), Czech Republic (Prague) and Denmark (Copenhagen). Depending on the specific local context, various stakeholders are perceived as essential to the decision-making process. The power relations and problems encountered in implementing public policy in particular locations have been summarised in three sections: relationships between stakeholders, leadership, and good practices. The paper concludes with a list of typical actors who should be involved in planning, building and managing a local service centre in an urbanised neigh-bourhood.